(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
In the last two decades, there was an extensive research focused on the study of synthetic amphiphilic vesicles, prepared by nonionic surfactants (niosomes). The particle size of these vesicles is critical for their intended therapeutic benefits. Formulation and processing factors affect greatly the physical characteristics of the resulted nanosystems. Therefore, the present work was adopted to investigate how proper manipulation of various formulations and processing factors on vesicular Z-average particle size. The selected variables were membrane additives, [including cholesterol (CHO), dicetylphosphate (DCP) and stearylamine (SA)], sonication time as well as drug loading factor (using mannitol and estradiol). Sorbitan monopalmitate (span 40) niosomes were prepared by the conventional thin film hydration method. Particle size, measured by Photon Correlation Spectroscopy, and polydispersity indices were measured and compared.The results indicated that CHO increased the vesicular size, with 2:1 and 1:1 (span 40:CHO) ratios showing the same size. Sonication reduced the vesicle size by 23, 35 and 42% after 10, 20 and 30 min, respectively. After 30 min, the effect of sonication was minor. The addition of charge inducing agents changed the zeta potential depending on the type of the additives. Surface charge increased the size by 24 and 11% when using DCP and SA, respectively. Drug incorporation increased the vesicle size to an extent based on its aqueous solubility. There were about 35 and 6.2% increase in vesicular size for estradiol and mannitol, respectively, supporting the partitioning of lipophilic drug within the fatty acyl side chains of the bilayer membrane.